The Taxation of High Income Earners - Shome, Parthasarathi (IMF Policy Discussion Papers; Policy Discussion Paper, 1993)
The 1980s trends were to lower marginal personal income tax rates, scale down rate structures, and apply the highest rate at lower levels of per capita GDP. In the 1990s, driven by fiscal deficits and unemployment, and difficulty in linking high marginal rates to low incentives or revenue productivity, tax authorities are again demonstrating an interest in increasing marginal rates. This will burden those that are correctly paying the tax. Instead, equity and revenue productivity should be improved through minimum taxes, presumptive taxes, adequate inclusion of capital income in the tax base, revitalization of property taxes, and selected luxury taxes.